A New Relativistic Wave Equation for a Massive Boson and Fermion System (2015)
This article pretends to show some results from the study of The Relativistic Wave Equation in order to describe a massive system of boson and fermion. We defined the scattering matrix Vf i on the electromagnetic case and concurrently we extended it to the strong and weak interactions of the vector meson with the fermions. We also studied some applications to hadronic physics ,Quantum Hadrondynamics (QHD-I) and neutrino physics.